Demoralization in breast cancer survivors - Sender, Annekathrin; Hinz, Andreas; Broemer, Laura; Mehnert-Theuerkauf, Anja; Strauß, Bernhard; Briest, Susanne; Rosendahl, Jenny (Frontiers in Psychology, 2025)
ObjectiveDemoralization is a state of existential distress and loss of meaning in life and often associated with poor quality of life in cancer survivors. This study aimed to test psychometric properties of the Demoralization Scale-II (DS-II), to compare demoralization in breast cancer survivors with scores obtained in the general population in Germany, and to identify prognostic factors for demoralization and associations with spiritual well-being and other related variables.MethodsWe analyzed a sample of 162 female breast cancer survivors (mean time since diagnosis 2.5 years) using the DS-II and a set of validated questionnaires measuring distress (DT), anxiety (GAD-7), depression (PHQ-9), fatigue (MFI-10), spiritual well-being (FACIT-Sp) posttraumatic growth (PTGI) as well as meaning and purpose (LAP-R). The DS-II mean scores of the survivor’s sample were compared with those of the general population. We performed t-tests, effect sizes, Cronbach’s alpha, correlations and a confirmatory factor analysis to achieve the study objectives.ResultsThe DS-II showed excellent psychometric properties, with an internal consistency of α = 0.92 for the total scale and α = 0.88 for the meaning and purpose subscale as well as α = 0.85 for the distress and coping subscale. Demoralization was highly correlated with the experience of meaning and peace (r = –0.79), sense of existential vacuum (r = −0.78), anxiety (r = 0.72), and depression (r = 0.70), while the correlations were lower for distress (r = 0.37) and post-traumatic growth (r = −0.19). The mean scores of the breast cancer survivors were markedly higher than those of the general population on both subscales distress and coping (d = 0.71) and meaning and purpose (d = 0.34).DiscussionThe results show that demoralization is prevalent in cancer survivors and should be understood as a proper construct that has multiple relationships with other variables of mental health. This underlines the need to establish evidence-based support programs that focus on demoralization and address these links.